Peran grit dan self efficacy terhadap work engagement pada tenaga kesehatan rumah sakit - Ratna Tri Hari Safariningsih; Mohamad Rizan; Agung Wahyu Handaru (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
This study aims to determine the role of grit and self-efficacy on work engagement for health workers at type C hospitals in Depok City. The data analysis used Structural Equation Modeling (SEM), namely Partial Least Square (PLS). The sample size in this study was 200 respondents. The results showed that grit positively and significantly affects work engagement. Grit has a positive and significant effect on self-efficacy. Self-efficacy has a positive and significant effect on work engagement. Self-efficacy mediates the relationship between grit which has a positive and significant effect on work engagement. Based on the Variance Accounted For (VAF) calculation, self-efficacy mediates partially. With self-efficacy, grit will affect increasing work engagement. This research can provide literature about the role of grit and self-efficacy on the work engagement of nurses at Type C Hospital. This research is helpful for hospitals in developing strategies to increase nurse work engagement.